(untitled) (International Journal of Engineering and Computer Science, 2017)
In this incessant science and technological era, where advances in web technology and the production of mobile devices and sensors connected to the Internet are resulting to voluminous amount of structured, semi-structured and unstructured data, called Big Data, the demand for technologies with extensive processing and storage requirements is rising to persuasively process such data i.e. Big Data. Traditional relational databases are facing challenges in meeting the performance and scale requirements of Big data. To meet these requirements enterprises are adopting diversified technologies like NoSQL and NewSQL which are emerging as alternative to relational database technologies for the various interrelated megatrends like Big Data and Cloud Computing. This paper discusses the prominent features of NoSQL and NewSQL data stores in the context of cloud computing.